An Analysis the Critical Successful Factors on Information Adoption during The Pandemic COVID-19 Outbreak - Mohammad Nurul Huda; Siti Mas Ruroh; Etry Novica Kurniasari (Risenologi, 2022)
The pandemic COVID-19 become an essential issue that has driven the high use of social media as a digital tool to disseminate information. There are two benefits of social media as digital communication. Accelerating the spread of true information effectively and efficiently and spreading misinformation about the pandemic COVID-19 is increasingly unstoppable. The great challenge faced by the government is to rebuild trust in government and trust in information quality by providing quality information. Provision of quality information is a government effort to promote healthy living as a strategy to support public health policies. This research investigated how the provision of quality information directly affects trust in information quality, trust in government, and information adoption. This research also examined the direct effects of trust in information quality, trust in government on information adoption. This research used a quantitative approach with an online survey to collect the data. The sample of this study was 160 samples. We used WrapPLS software version 7.0 to analyze the data and measure the hypothesis paths in this research model. The results of this study were the provision of quality information has positive effects on trust in government, trust in information quality, and information adoption; Trust in government has a positive effect on information adoption; and rejected the effect of trust in information quality on information adoption.